Shift in bacterial community structure in response to salinity in a continuous anaerobic ammonium oxidation (anammox) reactor. (February 2020) - Jeong, Dawoon; Kim, Weonjae; Lim, Hyunman; Bae, Hyokwan
Abstract: The effect of gradual salt adaptation on nitrogen removal performance was examined in a continuous flow anaerobic ammonium oxidation (anammox) process. Specific anammox activity (SAA) batch test was conducted to observe the effect of salinity shock loads. SAA rapidly reduced from 100% to 2.3% when salinity increased from 0 g.L −1 to 5.0 g.L −1 NaCl. On the contrary, high total nitrogen removal efficiency (TNRE) of 85% was obtained when salt concentrations gradually increased up to 25.0 g.L −1 NaCl, after 264 d of the continuous anammox operation. Then, the additional increase of salinity by 2.5 g.L −1 resulted in critical negative effect of 63.8% reduction in TNRE. Candidatus Jettenia sp. was dominant as a salt-tolerant anammox species in the salt ranges of 0–27.5 g.L −1 NaCl. In contrast, Candidatus Kuenenia stuttgartiensis was observed at 10–27.5 g.L −1 NaCl with smaller relative abundance than that of Ca . Jettenia sp. This indicates that Ca . Kuenenia sp. would build limited niche in the competition with Ca . Jettenia sp. under sudden increase of salinity stress. Interestingly, heterotrophic bacteria became dominant in autotrophic nitrogen removal process in response to the increase in salt concentration, which could be a cause of anammox system failure. Graphical abstract: Image 1 Highlights: Gradual increase in salinity enhanced a salt tolerance of freshwater anammox bacteria. High salinity of 20 g.L −1 caused alternation in anammox bacterial community. Ca. Jettenia sp. was more dominant than Ca. Kuenenia under the increased salinity. Ca. Kuenenia provided a limited niche for bacterial community change. Heterotrophic bacteria were abundant in autotrophic nitrogen removal process.